Three new centipede species of the genus Newportia Gervais, 1847 from Colombia (Scolopendromorpha, Scolopocryptopidae, Newportiinae) - Jiménez, Sebastian Galvis; Chagas-Jr., Amazonas (Zootaxa, 2023)
Three new species of the genus Newportia Gervais, 1847 from Colombia are described and illustrated. They were found in the cloud forests of the eastern Andes and in the rainforests of the biogeographical Chocó, ecosystems where the centipede fauna has been little studied. Newportia (Newportia) florezi sp. nov. differs from other Newportia species in the arrangement of the spinous processes on the prefemur of the ultimate legs, while Newportia (Newportia) anopla sp. nov. has a coxopleuron without any trace of a coxopleural process and possesses an atypically small forcipular coxosternite. Newportia (Newportia) tequendama sp. nov. is morphologically similar to Newportia pusilla Pocock, 1893, but differs in having an undivided tarsus 2 in the ultimate legs and the arrangement of the spinous processes on the prefemur and femur. An identification key for the Colombian species of Newportia is provided.